Ekologi Sastra pada Kumpulan Cerpen Berbahasa Madura Ngejung Karya Mat Toyu - Abdul Wafi; Suhairi Suhairi; Moh Khalid Hasan (Tadris Bahasa Indonesia, Fakultas Tarbiyah, Institut Agama Islam Negeri Madura, 2025)
This research aims to provide an understanding of the importance of caring for the environment through the study of ecological literature by analyzing literary elements in the short story collection